Determining thermodynamic parameters of aluminum X-pinch plasma; Technical Physics Letters; Vol. 39, iss. 1 - Artyomov A. P.; Fedyunin A. V.; Chaikovsky S. A.; Oreshkin V. I. Vladimir Ivanovich; Lavrinovich I. V.; Ratakhin N. A. Nikolay Aleksandrovich (2013, 2013)
Title screen